A BRIEF OVERVIEW OF CANDIDIASIS - Javeria Sharif; Ayesha Haidar; Ambreen Talib; Amara Ijaz; Sana Munawar; Uzma Bilal; Maryam Zahra; Bushra Anwar; Tehreem Rana; Ayesha Muazzam (JURIHUM : Jurnal Inovasi dan Humaniora, 2024)
Candidiasis is generally provoked by candida species, which is a fungal disease impacting different mucosal surfaces in the human body. This review provide a brief explanation on candidiasis, encircling its epidemiology, pathogenesis, clinical indications, diagnoses, and treatment. Candida, especially Candida albicans inhabit symbiotic microorganisms in the oral cavity, gastrointestinal tract, and genitalia. However, disturbances in host immunity, modifications in the microbiota, or the use of broad-spectrum antibiotics can lead to excessive growth, inducing candidiasis. Its widespread occurrence is significant in immunocompromised people, such as those with HIV/AIDS, and in patients acquiring immunosuppressive antidotes. The pathogenesis of candidiasis encompasses adherence of candida to host cells, followed by aggression and tissue deterioration. Candida has virulence factors, comprising adhesins and enzymes, adding to its proficiency to elude the host immune response. The yeast-to-hypha metamorphosis is critical for tissue aggression, additionally underlining the complicatedness of its pathogenic mechanism. Clinical indications of candidiasis fluctuate based on the site of the disorder. Oral candidiasis is illustrated as white, adherent patches on the mucosal surfaces, while genital candidiasis is demonstrated as vulvovaginal irritation and discharge. Systemic candidiasis can lead to harsh, life-threatening infections, particularly in immunocompromised patients. Diagnosis depends on clinical assessment, microbiological culture, and more recently, molecular strategies.